"I Was There" and "It Happened to Me": An Exploratory Study of Killing as an Adventure Narrative in the Accounts of Soldiers and Police Officers. Issue 3 (July 2019) - Baggaley, Katherine T.; Shon, Phillip C.; Marques, Olga
Various theoretical frameworks have been applied in an attempt to understand the phenomenon of killing. While previous studies have examined killing as an outcome-oriented measure, few have explored killing as a narrative. Using letters written by soldiers, police officers, and security professionals found in the magazine Soldier of Fortune, this study examines the reported behaviors that occur during the killing process and argues that the process of killing is best understood as an adventure narrative. Applicability of findings to other homicides is discussed.